Quantification of cone loss after surgery for retinal detachment involving the macula using adaptive optics. Issue 10 (3rd June 2014) - Saleh, M; Debellemanière, G; Meillat, M; Tumahai, P; Bidaut Garnier, M; Flores, M; Schwartz, C; Delbosc, B
Abstract : Aims: To image the cones in eyes with anatomically successful repair of retinal detachment (RD) involving the macula and in healthy fellow eyes using an adaptive optics (AO) camera and to correlate the results to clinical outcomes. Methods: Twenty-one patients (42 eyes) operated for macula-off RD were imaged 6 weeks after surgery using an AO camera (RTX 1, Imagine Eyes, Orsay, France). Cone density (cells/mm 2 ), spacing between cells (µm) and the percentage of cones with six neighbours were measured. Best-corrected visual acuity (BCVA) and thickness of the inner segment ellipsoid (ISe) band imaged by SD-optical coherence tomography were also measured. Results: The parafoveal cone density was decreased in eyes operated for RD (mean±SD 14 576±4035/mm 2 ) compared with fellow eyes (20 589±2350/mm 2 ) (p=0.0001). There was also an increase in cone spacing (10.3±2.6 vs 8.0±1.0.9 µm, respectively, p<0.0001). The nearest-neighbour analysis revealed a reduction in the percentage of cones with six neighbours (36.5±4.2 vs 42.7±4.6%, p=0.0003). The ISe thickness, thinner in the operated eyes, was correlated to the cone density (r=0.62, p<0.0001). BCVA was significantly correlated to cone density (r=0.8, p<0.001). Conclusions: There was a decrease in the cone density after RD with an estimated loss of one-third of the cones. Postoperative visual acuity was highly correlated with the cone density. AO may be a valuable prognostic tool after RD surgery.